2013
DOI: 10.1074/jbc.m112.445734
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Lipid Kinase PI4KIIα Activity and Lipid Raft Association of Presenilin 1 Underlies γ-Secretase Inhibition by Ginsenoside (20S)-Rg3

Abstract: Background:Cerebral elevation and accumulation of amyloid ␤-peptide is an invariant feature of Alzheimer disease. Results: Natural compound (20S)-Rg3, a PI4KII␣ activator, modulates ␥-secretase activity in lipid rafts by increasing levels of phosphoinositides. Conclusion: Activation of a key phospholipid synthetic pathway by a natural product regulates ␥-secretase activity. Significance: We identify a novel molecular mechanism for the regulation of ␥-secretase activity by (20S)-Rg3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
41
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 85 publications
3
41
0
Order By: Relevance
“…PI4KIIα has a specific cysteine-rich motif (-CCPCC-); its kinase activity critically depends on palmitoylation of the cysteine-rich motif152829 and is modulated by cholesterol, amyloid-β peptide, mastoparan, 25-hydroxycholesterol and ginsenoside (20S)Rg3 via changing the membrane environment as suggested previously14303132.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…PI4KIIα has a specific cysteine-rich motif (-CCPCC-); its kinase activity critically depends on palmitoylation of the cysteine-rich motif152829 and is modulated by cholesterol, amyloid-β peptide, mastoparan, 25-hydroxycholesterol and ginsenoside (20S)Rg3 via changing the membrane environment as suggested previously14303132.…”
mentioning
confidence: 85%
“…Its dysfunction contributes to tumour growth6, spastic paraplegia11, Gaucher’s disease12 and Alzheimer’s disease1314, suggesting PI4KIIα as a drug target.…”
mentioning
confidence: 99%
“…Of the 12 ginsenosides, CK, F 1 , Rh 1 , and Rh 2 were predicted to pass the BBB and ADMET analysis predicted toxic effects for ginsenosides Ro and ginsenoside Rg 1 , while Rf showed low oral absorption in human gastrointestinal tract. These results suggest that of the seven ginsenosides demonstrating BACE1 (Kang et al 2013) Rg 3 enhanced neprilysin (NEP, rate-limiting enzyme in A" degradation) gene expression. Caused a reduction in A"(1-40) and A"(1-42).…”
Section: Ginsengmentioning
confidence: 91%
“…Although in some cell types, PI(4)P production at the PM is performed by PI4KIII (Nakatsu et al, 2012), PI4KII has also been shown to control cellular levels of PI(4,5)P 2 (Pan et al, 2008;Chu et al, 2010;Kang et al, 2013). Indeed, despite the fact that in several cell types PI4KII localizes primarily to the transGolgi network and endosomes (Wang et al, 2003;Salazar et al, 2005;Balla and Balla, 2006;Minogue et al, 2006), a portion of PI4KII can be recruited to the PM (Wei et al, 2002;PizarroCerdá et al, 2007).…”
Section: Discussionmentioning
confidence: 99%